Robotic Technologies in Hospitality and Tourism: A PRISMA-Compliant Review on Guest Satisfaction Enhancement - Kumar, Ravi; Saifullah Khalid, Md; Agarwal , Sanskriti (PALASH A JOURNAL OF HOSPITALITY AND TOURISM SERVICE MANAGMENT, 2025)
This PRISMA-compliant systematic review examines how robotic technologies influence guest satisfaction in the hospitality and tourism industry. Focusing on both robotic and AI-driven systems, the study explores their roles not only in improving operational efficiency but also in enhancing emotional and experiential aspects of service. A total of 26 peer-reviewed articles were selected for Thematic content analysis was conducted using coding categories such as anthropomorphism, usefulness, contextual fit, and human– robot collaboration. The findings show that robots enhance efficiency, safety, and novelty, while AI technologies support personalization and adaptive service. However, guest satisfaction is highest in hybrid service models that integrate robotic precision with human emotional intelligence. Guest acceptance is shaped by several factors, including robot design, perceived value, cultural context, and the quality of interaction between guests and service robots.